Employee Performance at Bank Syariah Indonesia (BSI) KC. Panorama - Pipin Trisakti; Andang Sunarto; Aan Shar (Yayasan Darussalam Bengkulu, 2023)
This study aims to determine how employee performance at Bank Syariah Indonesia (BSI) KC Panorama. Syariah Indonesia (BSI) KC Panorama. This research is qualitatively based on a case study using the field research method (Field Research). The data sources used are primary data and secondary data. Data collection techniques used in this study are through interviews, observation, and documentation. The results of this research and discussion show that the performance of employees of Bank Syariah Indonesia (BSI) KC Panorama Bengkulu is good. This can be seen from the quality and quantity of work, attendance and punctuality, responsibility, punctuality, and cooperation of Bank Syariah Indonesia (BSI) KC Panorama Bengkulu employees. The cooperation of employees of Bank Syariah Indonesia (BSI) KC Panorama Bengkulu is quite good.